Samorząd gospodarczy a system decentralizacji administracji publicznej w Polsce - Kmieciak, Robert (Polityka i Społeczeństwo, 2020)
In studies of decentralization processes little is spoken of economic self-government, the role of which is to advocate the interests of the social environment of entrepreneurs. Since the beginning of the political transition in Poland an unproductive discussion has been ongoing concerning the place of economic self-government in the system of local government. Current legal regulations do not provide business chambers with the status of public legal unions. They tend to be based on the facultative nature of ties between entrepreneurs, which is the main cause of the weakness of Polish economic self-government, or rather the economic quasi-self-government. Undoubtedly, the lack of such structures in the sphere of public institutions is the main reason for their marginalization by the government and local authorities, which do not see the need to make any concessions for the distracted economic environment. Given this context, the most rational solution seems to be the creation of universal economic self-government, which will be incorporated in the system of public institutions.